OPTIMIZING THE RESPIRATORY HEALTH OF SOLDIERS DURING PASTURE BURNING - McGinley, Erica Christine (My University, 2015)
Pasture burning is a practice native to the Flint Hills Region of Kansas. Without fire, the tallgrass ecosystem would cease to exist because woody species, such as the red cedar, would overtake the land (1). Ranchers in the area participate in prescribed burning to revitalize the native prairie grasses for cattle consumption (2). Burning produces higher quality grasses, more weight gain in cattle, and more profit for the rancher (1). Prescribed fire benefits the grass and simultaneously causes air pollution; the most common pollutants associated with burning are particulate matter (PM) and ozone. These by-products of burning have demonstrated acute and chronic respiratory effects in human studies (3). The typical time-frame for burning in Kansas is relatively short, running from March to May. Plumes of pollution can form as ranchers burn simultaneously on days when weather conditions are favorable (1). Fort Riley, KS is a United States Army installation nestled in the Flint Hills. Its population has nearly doubled since 2005, bringing the total number of individuals on the fort to approximately 53,000 (4). This military population is required to perform many duties outdoors, resulting in a unique exposure to spring burning in the Flint Hills. This report compiles air quality data including concentrations of ozone, PM 2.5, and PM 10 from Riley and Shawnee Counties as well as data for medically coded respiratory conditions from Fort Riley beneficiaries. All data utilized came from the months of February, March, April, and May from years 2008-2011. Monthly averages from all data sets were analyzed by a mixed effects model. This report addresses the need for further investigation into potential confounding factors such as local pollen counts and respiratory illness from cold and flu season. It establishes the importance of future air quality data collection from a singular source and the need for additional and more complex studies on Fort Riley.
Keywords: Pasture burning; Flint Hills; Fort Riley; Public Health (0573)